Hippocampal Malformation and Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1998)
The MRIs of 13 members of two families with febrile convulsions (FC) and 10 members without FC were compared with 23 control subjects in a study at the Universities of Magdeburg and Bonn, Germany.